PENGARUH REPUTASI PERUSAHAAN TERKAIT EMISI GAS RUMAH KACA DAN TANGGUNG JAWAB SOSIAL TERHADAP NILAI PERUSAHAAN (Studi Empiris terhadap Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2014-2018) - Diah Novita Amalia; Daljono Daljono (Diponegoro Journal of Accounting, 2021)
This study aims to examine the effect of company reputation related to greenhouse gas emissions and social responsibility on firm value with control variables such as age, assets, liabilities and company operating income. The research population is manufacturing companies listed on the IDX in 2014-2018. The results of the sample selection obtained 33 companies that were used as the research object. The study was tested using SPSS 24 with multiple linear regression models. The independent variable is measured using content analysis with category assessment. The firm value which is also called market value is measured by multiplying the market price of the shares and the number of shares outstanding. The results showed that the company's reputation related to greenhouse gas emissions, corporate reputation related to social responsibility, age, assets and liabilities did not have a significant effect on company value. Meanwhile, operating income has a significant effect on firmvalue.